Understanding trends and shifts in rainfall in parts of northwestern India based on global climatic indices. (5th August 2016) - Narayanan, Priya; Basistha, Ashoke; Sachdeva, Kamna
Abstract : The spatial and temporal variability of rainfall patterns in the northwestern belt of India has been monitored over a period of 60 years (1949–2009). The trends and shifts in the data have been calculated using the Modified Mann‐Kendall test (MMK) and the Pettitt‐Mann‐Whitney test (PMW), respectively. To explain the shifts in rainfall at different stations in the northwestern region, the dominant climate indices were analysed for pre‐ and post‐shift years. The climate indices and rainfall distribution data were subjected to Principal Component Analysis (PCA) in order to understand the nature of rainfall distribution and the dominant indices related to its variability. The analysis of PCA results with respect to season shows that each station is influenced by one or more climatic factors; however, these factors are themselves influenced by other important atmospheric phenomena, such as western disturbances. The preliminary principle component analysis of rainfall data with respect to climatic indices indicates that Niño 3.4 and Pacific Decadal Oscillation (PDO) are the dominant climatic indices that have caused a shift in the rainfall pattern of western India, along with land use/land cover changes.